PANDEMI COVID-19 TONGGAK REKONTRUKSI MODEL PEMBELAJARAN MANDIRI DI ERA 4.0 - Harry, Musleh (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2022)
The Covid-19 pandemic has changed all aspects of people's lives, education has also been affected, learning that was once done in the classroom, now can only be done with an online system or a remote system. The purpose of this paper is to provide an overview of the differences between the learning system before and after the Covid-19 pandemic as well as a solution so that the learning system can run well. The method used in this paper is the normative method, while the result of this paper is that there must be a policy from the government regarding the reconstruction of the 4.0 era self-learning model during the current pandemic, and to achieve the expected system it must be supported by adequate facilities and aspects such as readiness from various parties such as teachers, students and parents.